Level of Difficulties of Working Solo Parents in Balancing Work and Child’s Education - Maro, Crisel Ermino; Estaras, Chloe Ann Donguez; Ermino, Ada Katherine Gonzales; Lelis, Meldred Jongco; Barola, Rene Cabrea (Jurnal Pendidikan Progresif, 2024)
Level of Difficulties of Working Solo Parents in Balancing Work and Child’s Education. Objectives: The study determined the level of difficulties of working solo parents in balancing work and child's education. Specifically, this made an inquiry on the  demographic profile of solo parents, child's educational activities they participated as well as their level of difficulty in balancing work and child's education. An output was made based on the result of the study.  Methods: Descriptive quantitative research method using survey through the use of survey-questionnaire with with 5-point Likert Scale,unstructured interview and data analysis were used with 25 working  solo parents as respondents.Frequency count, percentage, weighted mean and mean were used as statistical tools. Findings: It showed that most of the working solo parents were 31-40 years of age, females,working as housemaids,and attended Homeroom PTA Meetings.Moreover,they participated and attended different child’s educational activities. However, they had difficulty in participating the various child’s activities evident in the overall mean which was 2.76  interpreted as Moderate Difficulty.Conclusion: Ages 31- 40 were equipped in supporting their kids. Females had high propensity of being working solo parents as  housemaids which offered them steady income and job security. In addition, the working solo parents actively attended mandatory or required educational activities for their children.Due to their moderate difficulty in participating nemrous child’s school activities, a Solo Parent Self-Management Enhancement Plan was made as  output of the study. Keywords: working solo parents, solo parents, balancing work and child’s education, education.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024131